Enhancement of chlorhexidine activity against planktonic and biofilm forms of oral streptococci by two Croton spp. essential oils from the Caatinga biome. Issue 10 (26th November 2022) - Vasconcelos, Brendda Miranda; Pereira, Antônio Mateus Gomes; Coelho, Paulo Adenes Teixeira; Cavalcante, Rafaela Mesquita Bastos; Carneiro-Torres, Daniela Santos; Bandeira, Paulo Nogueira; da Silva, Felipe Ferreira; Rodrigues, Tigressa Helena Soares; Gomes, Geovany Amorim; Carneiro, Victor Alves
Abstract: This work investigates the ability of two Croton spp. essential oils (EO) to enhance chlorhexidine (CHX) activity against oral streptococci. EO's chemical composition of Croton argyrophyllus and C. pluriglandulosus was determined by GC-MS/FID. The microbial growth kinetics and minimum inhibitory concentration (MIC) of EOs and CHX were determined, followed by their synergism against S. mutans UA159 and ATCC 25175, S. salivarius ATCC 7073 and S. sp. ATCC 15300. The microplate-based method was used to determine the EO/CHX activity against 24-h-old biofilms. The major compounds were α-pinene (54.74%) and bicyclogermacrene (16.08%) for EOAr and 1, 8-cineole (17.41%), methyleugenol (16.06%) and elemicin (15.99%) for EOPg. Both EO had MIC around 16, 000 µg/mL. EOs/CHX presented a synergistic effect against most strains (FIC i from 0.133 to 0.375), and OE/CHX-treated biofilms showed a reduction in biomass and cell viability compared to CHX, only ( p < 0.01). Thus, the EOs works as natural adjuvants for CHX.